Weldability of a high entropy CrMnFeCoNi alloy. (November 2016) - Wu, Z.; David, S.A.; Feng, Z.; Bei, H.
Abstract: High-entropy alloys are unique alloys in which five or more elements are presented all in high concentrations. To determine its potential as a structural alloy, a model face-centered-cubic CrMnFeCoNi alloy was selected to investigate its weldability. Welds produced by electron beam welding show no cracking. The grain structures within the fusion zone (FZ) are controlled by the solidification behavior of the weld pool. The weldment possesses mechanical properties comparable to those of the base metal (BM) at both room and cryogenic temperatures. Compared with the BM, deformation twinning was more pronounced in the FZ of the tested alloy. Graphical abstract: